Successful Pregnancy Outcome in a Patient with Pompe Disease Receiving Enzyme Replacement Therapy: A Case Report and Review of the Literature - Nampoothiri, Sheela; Yesodharan, Dhanya; Kuthiroly, Shwetha; Puthenveettil, Nitu; Murali, Vinitha; Peethambaran, Priyanka; K, Radhamany; Kishnan, Priya S (Archives of Clinical and Medical Case Reports, 2022)
Pregnancy in a woman with Pompe disease should be considered to be high risk and requires close monitoring as pregnancy may worsen symptoms, or cause initial symptoms to progress. Clinical data regarding the use of Enzyme Replacement Therapy (ERT) during pregnancy in Pompe disease is available only for 13 patients and the continuation of ERT during lactation has been reported in only one case. We report a successful pregnancy outcome in a 21 year old primipara with juvenile Pompe disease who continued receiving ERT throughout the pregnancy and lactation. She delivered a healthy full term female infant following caesarean section. She experienced worsening of motor function in the third trimester of pregnancy, but regained motor skills to pre-pregnancy level 6 months following delivery. Breast feeding was continued while on ERT. We also report a second patient in whom the diagnosis of Pompe disease was confirmed 5 years after delivery. In review of history the patient was symptomatic since age 15 years. Review of the literature of the published data of pregnancy in Pompe disease with continuation of ERT did not show any adverse outcome for the fetus. We add to the literature, our experience of continuation of ERT throughout the pregnancy and lactation in a patient with Pompe disease. More data needs to be collected to address the understanding of use of ERT during pregnancy and lactation.